Complementary in‐situ electrochemical ICP‐OES and corrosion studies of hot‐formed zinc alloy coated steel. Issue 11 (21st April 2015) - Wiesener, M.; Schinkinger, B.; Grundmeier, G.
<x xml:space="preserve">Abstract</x> A spectroelectrochemical approach for the fundamental analysis of the cathodic corrosion behavior of hot‐formed zinc alloy coated steel based on the in‐situ combination of inductively coupled plasma‐optical emission spectroscopy (ICP‐OES) is presented. Complementary to the microscopic information on the alloy dissolution, line‐scans of the free corrosion potential were measured across welding spots with a scanning capillary cell (SCC) to illustrate both the change in the local coating integrity and the ability of the coating to cathodically protect possible defects in the welding spot area. These studies were performed as a function of the holding time during hot‐forming. The results of the coulometric ICP‐OES measurements and the potential line‐scans are in very good agreement and show that in‐situ ICP‐OES provides insight into the dissolution behavior of zinc alloys that goes far beyond standard electrochemical techniques such as coulometry alone. It could be shown that the hot‐forming induced alloying of zinc with iron leads to preferential dissolution of zinc in the initial phase and to a parallel dissolution of iron and zinc in the second phase. For zinc‐nickel alloys the initial preferential zinc dissolution leads to a fast de‐alloying and the dissolution of the nickel rich phase occurs at rather anodic potentials. The alloying of nickel into zinc coatings leads to an inhibition of the zinc dissolution and hence to a decrease of the cathodic corrosion protection ability. However, the zinc‐nickel coatings are more resistant to evaporation and the defect formation in the welding spot is less significant. It could be shown that under the same conditions an aluminum silicon alloy does not show a significant preferential anodic dissolution hinting at a negligible cathodic protection.